1982
DOI: 10.1099/0022-1317-59-1-111
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recombinant Plasmids to Investigate the Structure of the Human Cytomegalovirus Genome

Abstract: SUMMARYHuman cytomegalovirus (HCMV) DNA was digested with restriction endonucleases and the fragments characterized with respect to molecular weight and relative mole proportions. The terminal fragments were identified by digesting HCMV DNA with exonucleases before restriction endonuclease treatment and subsequent gel analysis. The HindlII fragments of HCMV DNA were cloned in Escherichia coli and recombinant plasmids were characterized by digestion with restriction endonucleases and by molecular hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 8 publications
4
52
0
Order By: Relevance
“…Based on restriction endonuclease analysis published earlier , analysis of cloned fragments in plasmids (D. Spector, personal communication) and overlapping cloned fragments (B. Fleckenstein & J. Collins, personal communication) and additional re-cleavage analysis by cross-blot hybridization (Weststrate, 1981), slightly modified physical maps for the AD169 DNA were obtained (Weststrate, 1981). These maps are largely consistent with the maps published recently by Oram et al (1982) and Spector et al (1982). Physical maps of the SG DNA were constructed using cross-blot hybridization experiments, identification of terminal fragments and double-digestion of fragments (Weststrate, 1981).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on restriction endonuclease analysis published earlier , analysis of cloned fragments in plasmids (D. Spector, personal communication) and overlapping cloned fragments (B. Fleckenstein & J. Collins, personal communication) and additional re-cleavage analysis by cross-blot hybridization (Weststrate, 1981), slightly modified physical maps for the AD169 DNA were obtained (Weststrate, 1981). These maps are largely consistent with the maps published recently by Oram et al (1982) and Spector et al (1982). Physical maps of the SG DNA were constructed using cross-blot hybridization experiments, identification of terminal fragments and double-digestion of fragments (Weststrate, 1981).…”
Section: Discussionsupporting
confidence: 92%
“…The terminal sequences (TRI and TR,) are repeated in this arrangement in an inverted form (IR1 and IRs). This model was also confirmed by restriction endonuclease analysis by Weststrate et al (1980), Oram et al (1982) and Spector et al (1982). By analogy with the structural organization of HSV-1 (Wi!kie, 1976), HSV-2 (Cortini & Wilkie, 1978) and bovine mammillitis virus (Buchman & Roizman, 1978) DNA, it could be derived from the molarity of the terminal fragments of AD169 DNA that the DNA molecules exist in four equimolar subpopulations which differ only in the relative orientation of the unique sequences.…”
Section: Introductionmentioning
confidence: 59%
“…The first restriction maps of HCMV DNA were mainly constructed by cross blot experiments using purified virion DNA (Weststrate et al, 1980;DeMarchi, 1981). This was made much easier when virion DNA was cloned in plasmids Oram et al, 1982;Spector et al, 1982) and cosmids , from which detailed physical gene maps could be derived (Fig. 1).…”
mentioning
confidence: 99%
“…These workers originally identified XbaI E by looking for a region of the Towne strain DNA that shared homology with BgllI c of HSV-2 and could rescue cells from senescence and thus transform them. Although virus DNA is not retained in HCMV strain AD169-transformed cells, it is retained in cells transformed by (Oram et al, 1982) shown to be responsible for morphological transformation by HCMV strain AD169. HB1 to HB6 are the BaraHI subfragments of HindllI E. The transcript mapping was taken from Jahn et al (1984).…”
Section: Morphological Transformation Of Cultured Cells Transformamentioning
confidence: 94%